P014 Untargeted serum metabolome in longitudinal Crohn's Disease (CD) cohort enrolled during remission shows strong individualized signature and CD-associated signals that are maintained also in patients who normalized their fecal calprotectin. (27th May 2021) - Levhar, N; Hadar, R; Braun, T; Efroni, G; Abramovich, I; Gottlieb, E; Sosnovski, K; Abass, H; Berger, T; Granot, M; Neuman, S; Selinger, L; et al.
Abstract: Background: The serum metabolome contains potential disease biomarkers, some of which are produced endogenously, and some are generated by the gut microbiome. We recently found that Crohn's Disease (CD) patients in remission still show significantly reduced gut microbial richness and increased dysbiosis compared to healthy controls ( PMID: 30741738). Methods: Serum untargeted metabolomics, fecal V4 16S microbial characterization, and fecal calprotectin were longitudinally tested in CD patients enrolled in remission. Metabolomics was performed on 139 samples (25 CD and 12 controls) by liquid chromatography coupled with Q-Exactive Orbitrap Mass Spectrometer (LC/MS), and Thermo Xcalibur was used for data acquisition. PERMANOVA on beta diversity was used to define factors affecting serum metabolome. Multivariate analyses in MaAsLin were applied for specific metabolites differential abundance (FDR<0.25) and to test for correlations with microbial diversity. Results: During 24-months of prospective follow-up, 11/25 of the CD patients, who started in remission, flared. PERMANOVA on the serum metabolomic data indicated subject-specific signals. Despite this, using multivariate analyses and controlling for age, gender, and subject, we identified specific metabolites that were significantly different between CD and controls. CD samples were significantly enriched for purine derivatives, simple sugars, histidine and oxalate, compared to healthy controls. In contrast, amino-acids, TCA cycle-related metabolites, saturated fatty acids and acylcarnitines were consistently downregulated in CD. Interestingly, most of those CD-associated metabolic signatures were similar between CD patients with mucosal healing (calprotectin <100) and those with elevated calprotectin (>100, Median 197; IQR 143, 300). Interestingly, α-ketoglutarate (aKG) and decanoic-acid were further downregulated in active samples compared to remission (q= 0.2 and 0.16, respectively). Looking into those metabolites in samples prior to the flare, flared patients showed a negative trend in aKG, and a significant reduction in decanoic acid pre-flare (p<0.05) in comparison to patients who remained in remission throughout. To link this with the gut microbial composition, we looked at correlations between the microbial alpha diversity (Faith's PD) and serum metabolites, and identified positive correlations with butyrate (r=0.39, p < 0.001) and cystine (r=0.25, p=0.037), and negative correlation with betaine (r=-0.35, p=0.003). Conclusion: CD patients in remission exhibit a distinct serum metabolic signature, which may be linked in part with the gut microbial diversity and composition. Several metabolite signals may precede disease flare.